Child health and nutrition in the Western Brazilian Amazon: population-based surveys in two counties in Acre State - Pascoal Torres Muniz; Teresa Gontijo de Castro; Thiago Santos de Araújo; Nara Barros Nunes; Mônica da Silva-Nunes; Erika Hellena Esther Hoffmann; Marcelo Urbano Ferreira; Marly Augusto Cardoso (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2007)
The article presents prevalence rates for malnutrition, intestinal parasitic infections, anemia, and iron deficiency in under-five children in a population-based cross-sectional survey performed in the urban area of two counties in the Western Brazilian Amazon, Assis Brasil (n = 200) and Acrelandia (n = 477). Available data included: (a) weight and height measurements, standardized as z-scores using the 1977 NCHS reference population, (b) diagnosis of current intestinal parasitic infection, (c) blood hemoglobin levels, and (d) plasma ferritin and soluble transferrin receptor levels. Overall prevalence rates of low weight-for-height, low weight-for-age, and low height-for-age were 3.7%, 8.7%, and 7.5%, respectively, with similar figures in the two towns. Intestinal parasites were detected in 32.5% children; helminths were uncommon. Anemia and iron deficiency were diagnosed in 30.6% and 43.5% of the children, respectively. Evidence of anemia was found in only 47.6% of the children with depleted iron reserves, indicating that hemoglobin measurement alone would severely underestimate the magnitude of iron deficiency in this population. In both towns, anemia and malnutrition were significantly more prevalent among children in the lowest socioeconomic stratum.